Transition from Online to Offline Learing during the Covid-19 Pandemic in SMAN 4 Kediri - Ayu Rahardini, Nimas (Universitas Nahdatul Ulama Surabaya, 2022)
During pandemic covid 19, students in different schools will face different problems in adapting the transition from online to offline learning. However, each school or class has different characteristics and obstacles. Therefore, this study would like to observe one of senior high schools in Kediri, East Java to find out the obstacles that could be found by the teachers and students based on teachers’ perception and classroom observation. The researcher used a qualitative descriptive approach in this study. The results show that the main problem is the students’ motivation in learning English. Besides, students’ condition at home and the use of gadgets during online learning also influence the students’ learning process even until the offline class is implemented again. The researcher also provides the recommendation strategy from some other studies to solve this kind of problem based on the observation and teacher’s interview. Considering, students’ intrinsic and extrinsic motivation in learning English are recommended. Gamification can be a good method to increase students’ motivation during the learning process.